KLARIFIKASI AL-DARWÃ®SH ATAS PANDANGAN ORIENTALIS TENTANG KONTRADIKSI AYAT AL-QURâ€™AN DENGAN KAIDAH NAHW - Tidjani, Amnah (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2014)
This paper will examine clarification Muhy al-Dîn al-Darwîsh against charges orientalistabout the authenticity of the Koran. Today, these allegations go back voiced by the Egyptian Coptic priest Zakaria Batrousin his book Tasâulât Hawl al-Qur?ân. One of the accused is the assertion that the Koran contains errors and defects in terms of language, as it is considered contrary to the rules nah}w. From here finally Zakaria concludes that the Koran is not the work of God, but a bouquet of Muhammad, because God could do no wrong. What does Zakaria is a fragment of a long journey Orientalist in reviewing the Eastern world, especially the Islamic religion who has written neatly in history. By writing the book I?râb al-Qur?ân al-Karîm wa Bayânuh, al-Darwish wanted to prove that what is alleged Zakaria just nonsense. This book is written with a light and easy to understand language readers, especially for the orientalists who lack the ability to understand the science nahw and Arabic literature